Intersectional Directions in Working Life Research—a Proposal - Mulinari, Paula; Selberg, Rebecca (Nordic Journal of Working Life Studies, 2013)
A central challenge to gender studies during the last 15 years has been the expanding field of intersectionality. The use of intersectional perspectives within working life research has explored how class, sexuality, and race difference affected women’s position in the labor market. The aim of this article is to argue for the need of including an intersectional perspective in the field of working life research. By taking our point of departure in the work of feminist scholars Joan Acker, Miriam Glucksmann, and Chandra Talpade Mohanty, we argue that an intersectional perspective can expand as well as challenge working life research. But we also argue that working life research in many ways can contribute to the field of intersectional studies, especially by placing issues of exploitation, distribution, and production at the core of intersectional analyses.